Both RyRs and TPCs are required for NAADP-induced intracellular Ca(2+) release - Gerasimenko, Julia V. (Cell Calcium, 2015)
Intracellular Ca(2+) release is mostly mediated by inositol trisphosphate, but intracellular cyclic-ADP-ribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP) are important messengers in many systems. Whereas cADPR generally activates type 2 ryanodine receptors (RyR2s), the NAADP-activated Ca(2+) release mechanism is less clear. Using knockouts and antibodies against RyRs and Two-Pore Channels (TPCs), we have compared their relative importance for NAADP-induced Ca(2+) release from two-photon permeabilized pancreatic acinar cells. In these cells, cholecystokinin-elicited Ca(2+) release is mediated by NAADP. TPC2-KO reduced NAADP-induced Ca(2+) release by 64%, but the combination of TPC2-KO and an antibody against TPC1, significantly reduced Ca(2+) release by 86% (64% vs. 86%, p < 0.0002). In RyR3-KO, NAADP-evoked Ca(2+) release reduced by ∼50% but, when combined with antibodies against RyR1, responses were 90% inhibited. Antibodies against RyR2 had practically no effect on NAADP-evoked Ca(2+) release, but reduced release in response to cADPR by 55%. Antibodies to RyR1 inhibited NAADP-induced Ca(2+) liberation by 81%, but only reduced cADPR responses by 30%. We conclude that full NAADP-mediated Ca(2+) release requires both TPCs and RyRs. The sequence of relative importance for NAADP-elicited Ca(2+) release from the all stores is RyR1 > TPC2 > RyR3 > TPC1 >> RyR2. However, when assessing NAADP-induced Ca(2+) release solely from the acidic stores (granules/endosomes/lysosomes), antibodies against TPC2 and TPC1 virtually abolished the Ca(2+) liberation as did antibodies against RyR1 and RyR3. Our results indicate that the primary, but very small, NAADP-elicited Ca(2+) release via TPCs from endosomes/lysosomes triggers the detectable Ca(2+)-induced Ca(2+) release via RyR1 and RyR3 occurring from the granules and the ER.